Theoretical Framework Construction and Practical Path of Exhibition Text Translation from the Perspective of Ecological Translation Studies - Wang, Chao; Yi, Li; You, Li; Miaomiao, Jia (Advances in Social Sciences Research Journal, 2025)
As the core information carrier of cross-cultural exhibition activities, the translation quality of exhibition texts directly determines the international communication effectiveness and commercial value of exhibitions. This paper takes the "adaptation-selection" theory of ecological translation studies as its core, combined with bilingual text cases from over 20 international exhibitions such as the China International Import Expo and the Hannover Messe in Germany, to systematically construct a theoretical framework for exhibition text translation featuring "translation ecological environment-three-dimensional conversion strategies-survival effects of translated texts". The study reveals that the essence of exhibition text translation lies in translators actively adapting to the complex ecosystem constituted by "source language texts-target readers-sociocultural contexts-communicative purposes". Through dynamic transformations across linguistic, cultural, and communicative dimensions, translated texts achieve effective "survival" within target contexts. This framework provides localized theoretical guidance for exhibition text translation practices and offers empirical support for the deepening application of ecological translation studies in the field of applied texts.